Effect of the time of the pre-fermentation maceration on the antioxidant capacity, carotenes, vitamin C of a fermented drink of aguaymanto (Physalis peruviana L.) to the mature state - Falcón Romero, Paula (2019)
The general objective was to determine the ratio of the time of pre-fermentative maceration of fermented beverages made with mature aguaymanto applying two temperature levels (ambient and 8 °C) and three times of pre-fermentative maceration (60, 30, 0 days) on the variation of the capacity antioxidant, vitamin C and carotenoid content at the time of bottling and after 90 days of maturation. The drinks were made by red winemaking. The relation of the time of the pre-fermentation maceration to -8 °C and without maceration on vitamin C was established: T0 > T1 > T2. The relation of the time of the pre-fermentation maceration at temperatures of-8 °C and without maceration on the carotenoids was established T2 > T1 > T0, he relation of the time of the pre-fermentation maceration at temperatures of -8 °C and without maceration on the antioxidant capacity was established T2 > T1 > T0. The Pearson coeficient ratio between the antioxidant capacity and the vitamin C content was -0, 217 indicating a low indirect linear dependence and with respect to the ratio of the antioxidant capacity and the carotenoid content variation 0.968 indicating a direct linear relationship highly significant